Identification of Bryophytes in Jumog Waterfall, Karanganyar, Central Java, Indonesia - Yasir Sidiq; Alanindra Saputra; Siti Kartika Sari (Biotropic : The Journal of Tropical Biology, 2019)
Indonesia, as a mega-biodiversity country, has a high diversity of bryophytes (Liverworts, Hornworts, and Mosses). In addition, a waterfall is one of the most optimum places for bryophytes to life. One of many waterfalls in Indonesia is Jumog Waterfall. It is located in Karanganyar Regency, Central Java. This study aimed to know the diversity of bryophytes in Jumog Waterfall, identify the species, and analyze the genetic relationship through the species based on morphological characters. The explorative method was used to collect the samples. Identification of species was done by comparing samples to the handbook of identification. The results were; (1) there were fifteen species that found in Jumog Waterfall; (2) The highest similarity among species was 90%. They were grouped in genus Fissidentales, Order Dicranales, and Order Hypnobryales. Then, The lowest similarity was 30.8%. They were between Funaria hygrometrica and Riccia fliutans. It distinguished liverwort, hornwort, and mosses